Application of Optimal Control on Mathematical Model of Drug Distribution with Education and Criminal Law Aspect - Padja, Merry Yulianti; Soemarsono, Annisa Rahmita; Fitria, Irma (Jurnal ILMU DASAR, 2024)
Drugs are substances that, when used, can impact the body, particularly the central nervous system/brain. Prolonged drug use can lead to various disorders affecting physical, psychological, and social functioning. Generally, drug use cases occur among teenagers due to a lack of education and low literacy levels about the dangers of drug. In this study, control efforts by modeling the problem of drug use will be studied. In this study, modeling the problem of drug users with control efforts will be studied. There were additional controls for preventing drug abuse through school education, contact prevention through security and healthy living campaigns, and the procedures to report all drug abuse activities. The Pontryagin Minimum Principle is used to shows that the optimal controls influence the level of drug user distribution.